Proposição de áreas prioritárias à restauração florestal visando o redesenho da paisagem na Amazônia Mato-Grossense - Soares, Diego Ruiz (2020)
Deforestation and fragmentation of tropical forests results in an agromosaic composed of forest remnants in an anthropized matrix. Restoration actions are essential in order to reestablish connectivity between fragments, in addition to rethinking the productive matrix that promotes contributions to ecosystems and the farmers inserted there. The objective of this work was to evaluate a landscape redesign based on proposals for priority areas for forest restoration, aiming at increasing the structural connectivity of the landscape and protection of water resources in the watershed of Ribeirão Pingo de Ouro, Nova Canaã do Norte, MT. The temporal evolution of forest cover in the microbasin was characterized, basead on orbital images from 1984 to 2019. From the digital elevation model, information plans for the área were constructed and was made a multicriterial evaluation (weighted linear combination method - WLC) in GIS environment, with a focus on prioritizing areas for forest restoration, using as criteria the topographic moisture index (TWI), the proximity of forest fragments larger than 1 ha) and the slope of the terrain. The scenarios with restoration of the most priority areas were analyzed according to contributions to the spatial structure of the landscape (metrics and landscape indexes) and to the protection of water resources. Visits were also made to twenty farming families in the Settlement Project Veraneio (where the watershed under study is partially inserted), who built, based on orbital images, maps of current agricultural uses on rural properties and possible changes in the systems of production and insertion of tree components. The priority areas obtained via WLC and inserted only in the properties visited and those subject to alterations indicated by the interviewees were evaluated comparatively from their spatial structure and protection of water resources. The microbasin is inserted into the regional historical context of converting the forest to areas of agricultural use, with pastures currently composing the landscape matrix. The use of the CLP promoted the categorization of priority areas for restoration in an efficient manner, indicating 9% of the watershed as areas with high and very high priority, contributing to the reduction of the isolation of forest fragments and the increase of structural connectivity of the landscape, in addition to identifying areas with greater potential for water saturation and intermittent and ephemeral channels, important elements from the point of view of the conservation of water resources. TWI was more important among the criteria, being relevant for the identification of hydrologically important areas. The adoption of silvopastoral systems was the main change pointed out by farmers, and, with less emphasis, the restoration of permanent preservation areas (natural regeneration and / or assisted using conventional or agroforestry systems) was also identified. In terms of increased forest cover and structural connectivity of the landscape, the scenario of restoration of these areas has intermediate contributions between the scenario with restoration of areas with very high priority and the one with high and very high priorities combined. The dominant presence of conventional pastures in the watershed requires reflections on the multifunctionality and conservation of biodiversity in agro-ecosystems. The changes in the landscape, both those mentioned by farmers and differentiated management in the areas that are the most important to restoration, have the potential to generate a more diverse and multifunctional agromosaic product, with greater sustainability of agricultural activity and gains for rural producers, in addition to increased coverage forestry and structural connectivity of the landscape.